Combination of CO2 and Q-switched Nd:YAG lasers is more effective than Q-switched Nd:YAG laser alone for eyebrow tattoo removal. (April 2015) - Radmanesh, Mohammad; Rafiei, Zohreh
Abstract: Background: The eyebrow tattoo removal using Q-switched lasers is usually prolonged. Other modalities may be required to enhance the efficacy and shorten the treatment course. Objective: To compare the efficacy of Q-switched neodymium-doped yttrium aluminum garnet (Nd:YAG) laser alone versus combination of Q-switched Nd:YAG and Ultrapulse CO2 lasers for eyebrow tattoo removal after a single session. Patients and methods: After local anesthesia, the right eyebrow of 20 patients was treated with Ultrapulse CO2 laser with the parameters of 4 J/cm 2 and 3.2 J/cm 2 for the first and the second passes. Both eyebrows were then treated with 1064-nm and 532-nm Q-switched Nd:YAG laser. The spot size and pulse duration were 3 mm and 5 nanoseconds for both wavelengths, and the fluence was 7 J/cm 2 for 1064 nm and 3 J/cm 2 for 532 nm. Results: The side treated with combination of Q-switched Nd:YAG and CO2 lasers improved 75–100% in 6 of 20 patients versus only 1 of 20 in the side treated with Q-switched Nd:YAG alone. Similarly, the right side in 13 of 20 patients showed more than 50% improvement with combination therapy versus the left side (the monotherapy side), where only 6 of 20 cases showed more than 50% improvement. The Mann–Whitney test was 2.85 for the right side and 1.95 for the left side ( P value = 0.007). Conclusion: Using Ultra pulse CO2 laser enhances the efficacy of Q-switched Nd:YAG laser in eyebrow tattoo removal.